Cardiac conduction disorders in six infants with "near-miss" sudden infant deaths. Issue 6087 (3rd September 1977) - Keeton, B R; Southall, E; Rutter, N; Anderson, R H; Shinebourne, E A; Southall, D P
Abstract : Cardiac conduction disorders caused sudden serious illnesses in six infants that might have been fatal if diagnosis and treatment had been delayed. These cases provide circumstantial evidence to support a link between cardiac conduction disorders and some sudden infant deaths. A further potential long-term effect of these disorders is illustrated in one child in whom psychomotor retardation seemed to develop after an episode of cerebral hypoxia that was probably by an arrhythmia associated with the Wolff-Parkinson-White syndrome. Cardiac conduction disorders may be detected by routine neonatal ECG screening, and it may therefore be appropriate to start prophylactic antiarrhythmic treatment in certain children before clinical signs develop.